2018
DOI: 10.1002/ccr3.1562
|View full text |Cite|
|
Sign up to set email alerts
|

Recurrent pericarditis as an extra‐intestinal manifestation of ulcerative colitis in a 14‐year‐old girl

Abstract: Key Clinical MessagePericarditis is a known complication of mesalazine in the treatment of ulcerative colitis. This case study illustrates that after diagnostic work‐up, pericarditis should not always be attributed to the use of mesalazine. It may be the presentation of an extra‐intestinal manifestation of ulcerative colitis. Restarting of mesalazine should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Clinical improvement was achieved after use of colchicine with an increase in the dose of steroid [ 16 ]. Additionally, in adult patients with UC complicated by myocarditis, administration of corticosteroids led to symptoms relief [ 17 , 18 , 19 ]. The authors of the reported cases proposed the concomitant administration of colchicine to prevent the recurrence of myocarditis [ 17 , 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical improvement was achieved after use of colchicine with an increase in the dose of steroid [ 16 ]. Additionally, in adult patients with UC complicated by myocarditis, administration of corticosteroids led to symptoms relief [ 17 , 18 , 19 ]. The authors of the reported cases proposed the concomitant administration of colchicine to prevent the recurrence of myocarditis [ 17 , 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…UC-related pericarditis that recurred regardless of treatment was reported in a 14-year-old patient who was administered corticosteroids and colchicine to treat and prevent pericarditis. All other reports of cardiac involvement were caused by 5-aminosalicylate or mesalazine, with most patients recovering after discontinuation of the responsible drug [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, in patients with suspected IBD, as in our case, NSAID should not be given because NSAID could induce or exacerbate the preexisting ulcerative colitis by inhibiting cyclooxygenase and decreasing prostaglandin synthesis, which is cytoprotective to the intestine [ 6 ]. Therefore, it is suggested that corticosteroid should be used as first-line therapy in IBD patients with acute pericarditis [ 7 ].…”
Section: Discussionmentioning
confidence: 99%